-8(m+6)=-35+5m

Simple and best practice solution for -8(m+6)=-35+5m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(m+6)=-35+5m equation:


Simplifying
-8(m + 6) = -35 + 5m

Reorder the terms:
-8(6 + m) = -35 + 5m
(6 * -8 + m * -8) = -35 + 5m
(-48 + -8m) = -35 + 5m

Solving
-48 + -8m = -35 + 5m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-5m' to each side of the equation.
-48 + -8m + -5m = -35 + 5m + -5m

Combine like terms: -8m + -5m = -13m
-48 + -13m = -35 + 5m + -5m

Combine like terms: 5m + -5m = 0
-48 + -13m = -35 + 0
-48 + -13m = -35

Add '48' to each side of the equation.
-48 + 48 + -13m = -35 + 48

Combine like terms: -48 + 48 = 0
0 + -13m = -35 + 48
-13m = -35 + 48

Combine like terms: -35 + 48 = 13
-13m = 13

Divide each side by '-13'.
m = -1

Simplifying
m = -1

See similar equations:

| 8d+8=7d+9 | | x+12=yforx | | 5x+7=-2+8x | | c/3=70 | | d^2-10d+26=8 | | 13x+14=-12 | | 9x^2+144x+576=0 | | 9x+28-7x=-3.3 | | 5n-3(n-8)=4+3n | | 4=w/12 | | y-5+5= | | 11-4a=-7(a-1)+1 | | -(2x+3)=-5+7x | | 3x-3-x-4x=5x+12-12x | | b^2-4b+1=-5 | | 9(y-1)=4y+4 | | -6(r+6)=-37-5r | | -6b-6b=8-4b-7b | | p+7=8 | | (-x)-2x=(-7) | | 2=2-7n-2n | | 3x+4-2x-x=4x-4 | | -2(5x+5)+2x-1=-43 | | -2+3x=-6+7(6x-5) | | 5/k=2/7 | | 20-22+3= | | 2n+40=2n+10 | | 10=x*(x+3x) | | 8/3=5/b | | 4(8n-3)=-12+7n | | n/7=4/3 | | X^2(2x+3y-6)= |

Equations solver categories